Generation of CHOPi012-A iPSC line from a patient with visceral myopathy-related chronic intestinal pseudo-obstruction - Sohaib K. Hashmi; Sabine Schneider; Alyssa L. Gagne; Jean Ann Maguire; Paul Gadue; Robert O. Heuckeroth; Deborah L. French (Stem Cell Research, 2023)
Visceral myopathies are debilitating conditions characterized by dysfunction of smooth muscle in visceral organs (bowel, bladder, and uterus). Individuals affected by visceral myopathy experience feeding difficulties, growth failure, life-threatening abdominal distension, and may depend on intravenous nutrition for survival. Unfortunately, our limited understanding of the pathophysiology of visceral myopathies means that current therapies remain supportive, with no mechanism-based treatments. We developed a patient-derived iPSC line with a c.769C > T p.R257C/+ mutation, the most common genetic cause of visceral myopathy. This cell line will facilitate studies of how the ACTG2 R257C heterozygous variant affects smooth muscle development and function.